2009
DOI: 10.1038/nchem.330
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-covalent interactions in electrocatalytic fuel-cell reactions on platinum

Abstract: The classic models of metal electrode-electrolyte interfaces generally focus on either covalent interactions between adsorbates and solid surfaces or on long-range electrolyte-metal electrostatic interactions. Here we demonstrate that these traditional models are insufficient. To understand electrocatalytic trends in the oxygen reduction reaction (ORR), the hydrogen oxidation reaction (HOR) and the oxidation of methanol on platinum surfaces in alkaline electrolytes, non-covalent interactions must be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

61
716
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(787 citation statements)
references
References 37 publications
61
716
2
8
Order By: Relevance
“…This analysis suggests that extending the stability range of the non-hydrated phase will prove beneficial in improving the overall ORR activity. The importance of non-hydrated OH for the ORR at high potentials explains the enhanced ORR activity of Pt in hydrophobic ionic liquids 8 , in the presence of certain aqueous ions 6,7 and on stepped surfaces with narrow terrace width 9,10 . The last is unexpected as step sites strongly bind OH, as indeed observed with a reduced activity for small Pt nanoparticles 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis suggests that extending the stability range of the non-hydrated phase will prove beneficial in improving the overall ORR activity. The importance of non-hydrated OH for the ORR at high potentials explains the enhanced ORR activity of Pt in hydrophobic ionic liquids 8 , in the presence of certain aqueous ions 6,7 and on stepped surfaces with narrow terrace width 9,10 . The last is unexpected as step sites strongly bind OH, as indeed observed with a reduced activity for small Pt nanoparticles 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, dehydrated environments 8 will by their very nature limit the hydration of any OH intermediates. Finally, as hydrogen bonding of H 2 O to OH can compete with direct ion-OH interactions 28 , specific ions in the electrolyte could limit the hydration of OH 6,7 . This new insight into the subtle interplay between non-covalent hydrophobic and hydrophilic interactions can inspire the design of new catalysts, not only for the ORR but also for other relevant electrochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 0.1 M perchloric acid (HClO 4 ) that dissociates only to form weakly adsorbing perchlorate ions has been chosen as a supporting electrolyte in acidic medium. In alkaline medium 0.1 M NaOH or 0.5 M KOH electrolyte is used and these solutions are freshly prepared to avoid gradual dissolution of glass [8] that had been observed to cause changes in voltammetric profiles [9].…”
Section: Electrochemical Cellmentioning
confidence: 99%
“…In alkaline medium, NaOH or KOH are commonly used as electrolytes. However, it is reported that the non-covalent interactions between the hydrated Na + cations and adsorbed OH species are stronger than with hydrated K + cations so that the OH ad -M + (H 2 O) x clusters block the active sites for the electrocatalytic reaction [42]. In the present thesis, 0.1 M HClO 4 and 0.1M KOH that form weekly adsorbing species were used as electrolytes for the characterization of MOR at PtRu-C catalysts (in acidic condition), and the ORR at N-doped CNMs (in alkaline condition), respectively.…”
Section: Electrochemical Characterization 321 Electrochemical Cellmentioning
confidence: 99%